The origin of β-strand bending in globular proteins. (December 2015) - Fujiwara, Kazuo; Ebisawa, Shinichi; Watanabe, Yuka; Fujiwara, Hiromi; Ikeguchi, Masamichi
Abstract Background Many β-strands are not flat but bend and/or twist. However, although almost all β-strands have a twist, not all have a bend, suggesting that the underlying force(s) driving β-strand bending is distinct from that for the twist. We, therefore, investigated the physical origin(s) of β-strand bends. Methods We calculated rotation, twist and bend angles for a four-residue short frame. Fixed-length fragments consisting of six residues found in three consecutive short frames were used to evaluate the twist and bend angles of full-length β-strands. Results We calculated and statistically analyzed the twist and bend angles of β-strands found in globular proteins with known three-dimensional structures. The results show that full-length β-strand bend angles are related to the nearby aromatic residue content, whereas local bend angles are related to the nearby aliphatic residue content. Furthermore, it appears that β-strands bend to maximize their hydrophobic contacts with an abutting hydrophobic surface or to form a hydrophobic side-chain cluster when an abutting hydrophobic surface is absent. Conclusions We conclude that the dominant driving force for full-length β-strand bends is the hydrophobic interaction involving aromatic residues, whereas that for local β-strand bends is the hydrophobic interaction involving aliphatic residues.